FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN USAHATANI BROKOLI (Brassica oleraceae) (Survei Terhadap Petani Brokoli di Kecamatan Pacet, Kabupaten Cianjur, Provinsi Jawa Barat) - Hasan Sopandi; Dety Sukmawati; Tuti Gantini; Agi Dahtiar; Njanjang Apandi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This study aims to determine the factors that influence the success of broccoli farming. This study uses a survey method on rice broccoli farmers. Respondents were determined by census as many as 70 farmers. The form of the research is verification and the analytical technique used is path analysis with two paths. Based on the results of the study, it was obtained that the social factors of broccoli farmers in Pacet Subdistrict consisted of dimensions/indicators including: age; formal education; farming experience; the burden of family dependents. Productivity was achieved, 12 tons/ha and R/C = 2.25. There is an influence of social factors and economic factors on the application of broccoli farming production technology. The magnitude of the influence is 55.10% and 2.95%, respectively. There is the influence of social factors, economic factors and the application of technology to the success of broccoli farming. The magnitude of each other effect is 0.16%; 47.47% and 56.18%.